Model Filantropi Islam Green Waqf sebagai Instrumen Keberlanjutan dalam Perspektif SDGs dan Maqāṣid al-Sharī‘ah - Puput Adela Tavera; Muhtadi Ridwan; Ahmad Djalaludin (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
Green waqf is a contemporary development of Islamic endowment that integrates sharia principles with environmental conservation and sustainable development objectives. This article aims to analyze the concept of green waqf within the framework of Islamic economics and modern philanthropy, and to explain its relevance to the achievement of several Sustainable Development Goals (SDGs), particularly SDG 4, SDG 8, SDG 13, SDG 15, and SDG 17. This study employs a library research method by reviewing academic literature, official reports, and national policies related to waqf and environmental sustainability. The findings reveal that green waqf has strategic potential as a sustainable financing instrument that delivers long-term ecological, social, and economic benefits. Green waqf supports environmental conservation, eco-based economic empowerment, environmental education, and multisectoral partnerships. Furthermore, the concept aligns with the objectives of maqāṣid al-sharī‘ah, particularly the protection of life (ḥifẓ al-nafs), wealth (ḥifẓ al-māl), and the environment (ḥifẓ al-bi’ah), thereby providing strong sharia legitimacy for environmentally oriented waqf practices. Nevertheless, the implementation of green waqf still faces challenges, including weak governance structures, limited capacity of nazhir, and low literacy in modern financial instruments. Therefore, strengthening institutional capacity and enhancing cross-sector collaboration are essential for optimizing green waqf as an effective Islamic philanthropic instrument to support sustainable development in Indonesia.